From Impressions to Expectations: Assessment as a Form of Style Pedagogy - Medzerian, Star Allyn (The University of Arizona., 2010)
Recovering from a steady decline since the late 1980s, style is finding relevance in current approaches to composition pedagogy that make writing its focus. Yet despite this renewed interest in style and more general turn toward language study in rhetoric and composition, scholarship on style continues to be guided by a narrow view of what constitutes style pedagogy. This dissertation argues that in many composition classrooms, where style instruction is not prioritized, teachers' assessments of student writing can stand in for style instruction and become the primary means through which style is taught. What this suggests is that style is often taught implicitly, with little consciousness on the part of the teacher. As a result, style may be caught between conflicting values, those that are communicated to students through written feedback and grades and those that teachers actually endorse. This dissertation approaches the issue of style assessment from the perspectives of assessment scholarship, composition teachers, and advanced composition students to better understand how style is being "taught" through assessment and what values guide those evaluations. Ultimately, it seeks to extend the notion of pedagogy to include the assessment of students' writing styles and to contribute a more fully-realized treatment of style to its recent revival in rhetoric and composition.